Extraction and virulence analysis of melanin from Fonsecaea monophora - Huan HUANG; Minying LI; Mingfen LUO; Yinghui LIU; Qian LI; Xiaoyue WANG; Dongmei LI; Hongfang LIU; Liyan XI (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2023)
Objective To construct a mouse model of footpad inoculation with Fonsecaea monophora (F.monophora) melanin, and to analyze the differences in the virulence of F.monophora melanin from different sources. Virulence of F.monophora melanin and its influencing factors were also assessed. Methods F.monophora melanin was extracted by chemical digestion and acid-base method, and a mouse model of footpad melanin inoculation was constructed. Mice were divided into PBS group, chemical digestion group, acid-base group, and synthetic melanin group. The severity of mouse footpad swelling was measured. HE staining was performed to observe inflammatory cell infiltration and semi-quantitative analysis was performed. Results F.monophora melanin was successfully extracted. The chemical digestion method preserved the spatial morphology of melanin in the cell wall. In comparison to acid-base method, melanin extracted with chemical digestion method induced stronger and long-lasting footpad swelling, and more intense inflammatory reaction. Aggregation of neutrophils and macrophages was observed one day after injection of melanin. Seven days after injection of melanin, infiltration of neutrophils, macrophages and lymphocytes was observed. However, synthetic melanin group did not cause significant footpad swelling nor infiltration of neutrophils and lymphocytes although a small number of macrophages were seen. Conclusions The extracted F.monophora melanin can induce dramatic, inflammatory responses in mouse footpads. The complex spatial structure of melanin is associated with virulence, and synthetic melanin cannot mimic the virulence effects of F.monophora. Melanin extracted with chemical digestion method has advantages for study of fungal melanin virulence.